Influence of preparation procedures on the phenolic content, antioxidant and antidiabetic activities of green and black teas - Almeida, Tânia Santos de (2019)
The influence of common tea preparation procedures (temperature, infusion time, consumption time interval and tea bag/loose-leaf) and the type of water used, on the total phenolic content (TPC), the radical scavenging activity and the alpha-glucosidase inhibitory activity were assessed. Higher TPC and antioxidant activity were obtained when using lower mineralized waters. Tea bags also evidenced higher antioxidant activity than loose-leaf samples. Under the same conditions (90 degrees C and five minutes of infusion time) green tea contains almost twice the quantity of polyphenols and the free radical scavenging ability of black tea. In the alpha-glucosidase assay all infusions were active (97-100 %). Furthermore, HPLC allowed to identify some of the polyphenols present in both teas and to monitor their composition change with time. After twenty-four hours, the antioxidant activity was maintained without significant changes, but a small decrease in enzyme inhibition was observed, although this activity was still very high.